Experimental Investigation of Blast-Induced Crack Propagation Based on Digital Image Correlation Analysis - Carlota R. San Miguel; Nikolaos Petropoulos; Changping Yi; Daniel Johansson (Shock and Vibration)
Blasting is widely used in civil and mining engineering projects, with the side effect of introducing damage to the remaining rock. The damage can be differentiated from the cracks in the remaining rock, which increases the concerns of safety and requirements for rock support. In situ study of crack development remains complicated and costly; therefore, small-scale blasting experiments are a viable alternative for a detailed investigation of the crack propagation behavior. To fill the gap, this study examined a small-scale blasting test by investigating the velocity of the cracks implementing the digital image correlation (DIC) technique and avoiding contact methods such as strain gauges. An ultra-high-speed camera (UHSC) was used to record the blasting test in a single blasthole rock-like sample with a PETN cord. The experimental design underwent calibration until achieving the configuration of the equipment while ensuring the safety distance. The developed experimental methodology was tested successfully capturing the crack behavior. The analysis outcomes showed that the raw UHSC data needed to be preprocessed to enhance the tracking of cracks with the DIC method. The findings of the DIC data analysis indicated a fluctuation in the propagation velocity along the cracks (889–1129 m/s), revealing that the proposed methodology positively contributes to the propagation behavior of using the DIC method to track the blast-induced cracks.